1978
DOI: 10.1007/bf01273271
|View full text |Cite
|
Sign up to set email alerts
|

Primary familial amyloidosis with vitreous opacities

Abstract: A 41-year-old Japanese male with a new type of primary familial amyloidosis was reported. The patient developed vitreous opacities, and later, disturbances in the gastrointestinal and nervous systems. At autopsy, amyloid was observed in the vitreous and the retinal vessels. There were extensive cerebral infarcts and heavy meningo-vascular amyloid deposition. Although the postmortem study revealed slight peripheral nerve degeneration in the lower extremities secondary to amyloid deposition, there was no clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The one syndrome of amyloidosis in which the viscera and the CNS are linked has already been mentioned. 67 " 69 It is an extremely rare condition, described in both the USA (in a family of German origin) and Japan, of widespread vascular amyloid in multiple organs, vitreous amyloid (also of vascular origin) and severe leptomeningeal amyloid deposition. In the brain, however, only meningeal vessels show amyloid in their walls, and parenchymal CAA is rarely seen.…”
Section: Familial Caa and Related Syndromesmentioning
confidence: 99%
“…The one syndrome of amyloidosis in which the viscera and the CNS are linked has already been mentioned. 67 " 69 It is an extremely rare condition, described in both the USA (in a family of German origin) and Japan, of widespread vascular amyloid in multiple organs, vitreous amyloid (also of vascular origin) and severe leptomeningeal amyloid deposition. In the brain, however, only meningeal vessels show amyloid in their walls, and parenchymal CAA is rarely seen.…”
Section: Familial Caa and Related Syndromesmentioning
confidence: 99%
“…A review of the literature on FAP autopsy studies stressed amyloid deposition in peripheral nerves, heart, kidney, meninges, skin and ocular tissues [Silva-Horta et al, 1964;Hofer and Andersson, 1975;Ogata et al, 1978], The present case presented autopsy features simi lar to those described in a 41-year-old patient from a Japanese FAP family developing disturbances in the gastrointestinal and nervous system and showing heavy amyloid deposition in the vitreous [Ogata et al, 1978],…”
Section: Commentmentioning
confidence: 86%
“…In a number of studies from different countries, patients with ocular amyloidosis have shown the TTR met-30 mutation to be the most frequent of the known mutations, sometimes with neurological involvement. 3,[12][13][14][15][16][17] A major review on the subject of ocular amyloidosis 16 and a clinical pathological review 17 further highlight the various views on amyloidosis with ocular manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is usually associated with primary familial systemic amyloidosis [1][2][3] and has rarely been reported in the primary nonhereditary form. 4 -7 The diagnosis has often eluded both internists and ophthalmologists not only due to the disparity in the panorama of diseases in various countries but also due to the numerous mimics of vitreous amyloidosis, some examples being vitritis, old haemorrhage, familial vitreous degenerations, and particularly vasculitis.…”
mentioning
confidence: 98%